THE LEAF COLOUR OF MANGROVE (Rhizophora mucronata Lamk) IN TERMS OF ENVIRONMENTAL FACTORS IN MANGROVE FOREST OF MOJO VILLAGE, PEMALANG, INDONESIA - Niniek Widyorini; Siti Rudiyanti; Suryanti Suryanti; Churun Ain; Untung Ismoyo (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2021)
Mangrove (Rhizopora mucronata) is one kind of mangrove vegetation that planted on rehabilitation area of Mojo village’s mangrove forest. This species was choosen due easily obtained and sowed so that it dominated in the location. This research aimed to know the conditioning aspect from its leaves color and environmental factors from September - October 2019 in the Mojo village's mangrove forest. A total of 405 leaf samples were chosen in the same condition and derived from three research ie the zone closest to the sea, the zone closest to the river and the Central Zone. The leaf tip has the highest range of leaves color than the other leaf parts. Based on two-way ANOVA analysis, the observed zones having a difference of each other also the observed leaf parts too, while the interaction of them having no distinction significantly. The average color value on the part of the upper leaf surface was 115.3º and the under leaf surface was 88.55º more dynamic than the undersurface. The result of Pearson's correlation analysis was 0,396 that means low. Based on PCA analysis, the leaf color on the part of the upper leaf surface was negatively correlated with soil salinity in the location.